2005
DOI: 10.1007/s00467-005-2118-z
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic calcium and vitamin D treatments in steroid-treated children with nephrotic syndrome

Abstract: Steroid treatment has several side effects, including the deterioration of the bone and mineral metabolism in children with nephrotic syndrome. This randomized prospective study was conducted to determine the effects and prophylactic role of calcium plus vitamin D treatment on bone and mineral metabolism in children receiving prednisolone treatment. 40 children (27 boys and 13 girls) with NS (18 new onset and 22 relapsing) were included in the study. Their mean age was 4.6+/-1.8 years. All patients received pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 32 publications
(29 reference statements)
1
50
0
3
Order By: Relevance
“…A number of studies have shown a significant decrease in LS BMD Z-scores in the first few weeks of GC therapy, both in children [36] and in adults [10] with NS. These observations are attributable to the acute effects of GC on bone, as demonstrated in animal models [37], and on trans-iliac bone specimens from adults [38].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown a significant decrease in LS BMD Z-scores in the first few weeks of GC therapy, both in children [36] and in adults [10] with NS. These observations are attributable to the acute effects of GC on bone, as demonstrated in animal models [37], and on trans-iliac bone specimens from adults [38].…”
Section: Discussionmentioning
confidence: 99%
“…First, it is well-known that GCs have a predilection for interference with trabecular bone architecture, both in humans [6] and in animal models [5]. Furthermore, bone resorption markers increase acutely in adults with NS following administration of GCs [28], and are associated with a significant decline in spine BMD after a few weeks of therapy in both adults [28] and children with NS [9]. In addition, spine BMD has been shown to decline rapidly in adults following GC initiation for organ transplantation [29].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, reductions in lumbar spine areal bone mineral density (LS BMD) have been documented during the initial high-dose GC treatment phase in children with NS [9,10], and modest deficits in LS bone mineral content have been shown following years of intermittent GC therapy for steroid-sensitive disease [11]. Overt bone fragility manifesting as vertebral fractures has also been reported in children with NS following the initial GC treatment phase in the context of a treatment study [10], and later in the disease course [12].…”
Section: Introductionmentioning
confidence: 91%
“…Vários autores demonstraram que, quando os pacientes em uso prolongado de GC recebem suplementação de cálcio e vitamina D, os efeitos deletérios sobre o osso não ocorrem 56,57 ou são minimizados 58,59 .…”
Section: Cálcio E Vitamina Dunclassified
“…As alterações no crescimento e mineralização óssea que ocorrem nos pacientes em uso prolongado de doses suprafisiológicas de GC podem ser evitadas com a nutrição adequada, suplementação de cálcio e de vitamina D 58,59 , exercícios físicos (mobilidade normal), favorecimento da evolução normal da puberdade e de um intacto eixo GH-IGF-1 49 . Caso as alterações ocorram, tanto a alteração do crescimento longitudinal quanto a baixa massa óssea induzida pelos GC são reversíveis após suspensão do mesmo, …”
Section: Conclusõesunclassified